Peran Platform Pembelajaran Online Berbasis Ai dalam Meningkatkan Motivasi Belajar Siswa di Masa Pendidikan Digital - Suwanti, Riut; Sefnisari Candranita; Selvi Yani; Shilva Afriani (JPT : Jurnal Pendidikan Tematik, 2025)
Education has changed significantly with the advancement of technology, especially with the emergence of artificial intelligence (AI)-based online learning platforms. This article discusses how these platforms can improve students’ learning motivation in the digital era. By leveraging AI technology, learning platforms can provide a more personalized and interactive learning experience. Features such as personalization of materials, real-time feedback, and gamification help students feel more engaged and motivated. Research shows that students who use AI-based platforms tend to be more motivated because they can learn according to their needs and learning styles. However, there are also challenges that need to be addressed, such as the digital divide and data privacy issues. Therefore, it is important for educators and developers to ensure that this technology is used in an equitable and inclusive manner. Overall, this article concludes that AI-based online learning platforms have great potential to improve students’ learning motivation, but also require attention to the challenges that exist. Further research is needed to understand the long-term impact of using this technology in education. It is hoped that these findings can help create a better learning environment for students around the world.